MRI-ARSACS: an imaging index for autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) identification based on the multicenter PROSPAX study - Scaravilli, Alessandra; Negroni, Davide; Senatore, Claudio; Ugga, Lorenzo; Cosottini, Mirco; Ricca, Ivana; Bender, Benjamin; Traschütz, Andreas; Başak, Ayşe Nazli; Vural, Atay; van de Warrenburg, Bart P.; Durr, Alexandra; et al. (Movement disorders, 2024)
Background Autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) and hereditary spastic paraplegia type 7 (SPG7) represent the most common genotypes of spastic ataxia (SPAX). To date, their magnetic resonance imaging (MRI) features have only been described qualitatively, and a pure neuroradiological differential diagnosis between these two conditions is difficult to achieve. Objectives To test the performance of MRI measures to discriminate between ARSACS and SPG7 (as an index of common SPAX disease). Methods In this prospective multicenter study, 3D-T1-weighted images of 59 ARSACS (35.4 ± 10.3 years, M/F = 33/26) and 78 SPG7 (54.8 ± 10.3 years, M/F = 51/27) patients of the PROSPAX Consortium were analyzed, together with 30 controls (45.9 ± 16.9 years, M/F = 15/15). Different linear and surface measures were evaluated. A receiver operating characteristic analysis was performed, calculating area under the curve (AUC) and corresponding diagnostic accuracy parameters. Results The pons area proved to be the only metric increased exclusively in ARSACS patients (P = 0.02). Other different measures were reduced in ARSACS and SPG7 compared with controls (all with P ≤ 0.005). A cut-off value equal to 1.67 of the pons-to-superior vermis area ratio proved to have the highest AUC (0.98, diagnostic accuracy 93%, sensitivity 97%) in discriminating between ARSACS and SPG7. Conclusions Evaluation of the pons-to-superior vermis area ratio can discriminate ARSACS from other SPAX patients, as exemplified here by SPG7. Hence, we hereby propose this ratio as the Magnetic Resonance Index for the Assessment and Recognition of patients harboring SACS mutations (MRI-ARSACS), a novel diagnostic tool able to identify ARSACS patients and useful for discriminating ARSACS from other SPAX patients undergoing MRI.